Rapid Transfer of Plant Photosynthates to Soil Bacteria via Ectomycorrhizal Hyphae and Its Interaction With Nitrogen Availability - Gorka, Stefan; Dietrich, Marlies; Mayerhofer, Werner; Gabriel, Raphael; Wiesenbauer, Julia; Martin, Victoria; Zheng, Qing; Imai, Bruna; Prommer, Judith; Weidinger, Marieluise; Schweiger, Peter; Eichorst, Stephanie A.; et al. (Frontiers in Microbiology, 2019)
Plant roots release recent photosynthates into the rhizosphere, accelerating decomposition of organic matter by saprotrophic soil microbes (’rhizosphere priming effect’) which consequently increases nutrient availability for plants. However, about 90% of all higher plant species are mycorrhizal, transferring a significant fraction of their photosynthates directly to their fungal partners. Whether mycorrhizal fungi pass on plant-derived carbon (C) to bacteria in root-distant soil areas, i.e. incite a ‘hyphosphere priming effect’, is not known. Experimental evidence for C transfer from mycorrhizal hyphae to soil bacteria is limited, especially for ectomycorrhizal systems. As ectomycorrhizal fungi possess enzymatic capabilities to degrade organic matter themselves, it remains unclear whether they cooperate with soil bacteria by providing photosynthates, or compete for available nutrients. To investigate a possible C transfer from ectomycorrhizal hyphae to soil bacteria, and its response to changing nutrient availability, we planted young beech trees (Fagus sylvatica) into ‘split-root’ boxes, dividing their root systems into two disconnected soil compartments. Each of these compartments was separated from a litter compartment by a mesh penetrable for fungal hyphae, but not for roots. Plants were exposed to a 13C-CO2–labeled atmosphere, while 15N-labeled ammonium and amino acids were added to one side of the split-root system. We found a rapid transfer of recent photosynthates via ectomycorrhizal hyphae to bacteria in root-distant soil areas. Fungal and bacterial phospholipid fatty acid (PLFA) biomarkers were significantly enriched in hyphae-exclusive compartments 24 h after 13C-CO2–labeling. Isotope imaging with nanometer-scale secondary ion mass spectrometry (NanoSIMS) allowed for the first time in situ visualization of plant-derived C and N taken up by extraradical fungal hyphae, and in microbial cells thriving on hyphal surfaces. When N was added to the litter compartments, bacterial biomass and the amount of incorporated 13C strongly declined. Interestingly, this effect was also observed in adjacent soil compartments where added N was only available for bacteria through hyphal transport, indicating that ectomycorrhizal fungi were acting on soil bacteria. Together, our results demonstrate that (i) ectomycorrhizal hyphae rapidly transfer plant-derived C to bacterial communities in root-distant areas, and (ii) this transfer promptly responds to changing soil nutrient conditions.